APPLICATION OF DIRECTIONAL CURRENT PROTECTION FOR DETECTION OPEN PHASE LOADING MODES IN THE GRIDS WITH EFFICIENTLY GROUNDED NEUTRAL - Burbelo, Mykhailo; Melnytchyk, Sergiy; Emelianov, Olexiy (Scientific Works of Vinnytsia National Technical University, 2015)
The paper analyzes the values, directions and relations of conventional power of zero and negative sequence in longitudinal asymmetry modes. The possibility of such values application for protection of grids with efficiently grounded neutral is proved. For the protection against open-phase modes the directed protection of conventional power of negative sequence, operating after determining the argument of these powers in p-reset sectors of complex plane is suggested to use. REFERENCES 1. Правила улаштування електроустановок. – Xарків : Вид-во «Форт», 2011. – 736 с. 2. Вагнер К. Ф. Метод симметричных составляющих / К. Ф. Вагнер, Р. Д. Эванс. – ОНТИ НКТП СССР, 1936. – 407 с. 3. Нагай В. И. Релейная защита ответвительных подстанций электрических сетей / Нагай В. И. – М. : Энергоатомиздат, 2002. – 312 с.